Suppression of transcription factor early growth response 1 reduces herpes simplex virus lethality in mice - Chen, Shih-Heng (American Society for Clinical Investigation, 2008)
Herpes simplex virus type 1 (HSV-1) infection is the most common cause of sporadic, fatal encephalitis, but current understanding of how the virus interacts with cellular factors to regulate disease progression is limited. Here, we show that HSV-1 infection induced the expression of the cellular transcription factor early growth response 1 (Egr-1) in a human neuronal cell line. Egr-1 increased viral replication by activating promoters of viral productive cycle genes through binding to its corresponding sequences in the viral promoters. Mouse studies confirmed that Egr-1 expression was enhanced in HSV-1–infected brains and that Egr-1 functions to promote viral replication in embryonic fibroblasts. Furthermore, Egr-1 deficiency or knockdown of Egr-1 by a DNA-based enzyme greatly reduced the mortality of HSV-1–infected mice by decreasing viral loads in tissues. This study provides what we believe is the first evidence that Egr-1 increases the mortality of HSV-1 encephalitis by enhancing viral replication. Moreover, blocking this cellular machinery exploited by the virus could prevent host mortality.